Torsion of the omentum. A rare cause of acute abdomen - López-Colombo, Aurelio; Montiel-Jarquín, Álvaro; García-Carrasco, Mario; Nava, Arnulfo; Árcega-Domínguez, Arturo; Martínez-Fernández, Rodolfo; Suárez-Cuayahuitl, Israel (Revista Médica del Instituto Mexicano del Seguro Social, 2021)
Objective: To describe the clinical aspects, treatment and evolution of acute abdomen caused by torsion of the greater omentum.Methods: Retrospective analysis study consisted of a group of eleven patients with acute abdomen caused by torsion of the greater omentum. The variables included were age, sex, body mass index (BMI), clinical picture, evolution time, laboratory tests, radiology and treatment. Descriptive statistical analysis was employed.Results: Seven (63.6 %) women and four (36.36 %) men; mean age 33 (20 to 58) years; BMI > 25.0 in nine (81.81 %); average evolution 6.54, SD 3.47 days. All presented abdominal pain, six (54.5 %) abdominal distension, four (36.3 %) walking difficulty, three (27.27 %) general malaise, ten (90.9 %) slight leucocytosis, five (45.4 %) previous surgery. In all cases diagnosis was made by laparotomy, treatment was resection of the affected segment, and no complications were seen.Conclusions: Segmental torsion of the greater omentum is a rare cause of acute abdomen. Pain is the most frequent symptom, and the condition resembles acute appendicitis. It is often discovered during surgery and is treated by the removal of the affected omentum segment.